Tổng hợp và khả năng ứng dụng nanocompozit polynaphtylamin/Fe3O4 trong xử lí asen - Thi, Trần Minh; Trung, Vũ Quốc; Hoan, Phạm Văn; Thanh Hương, Vũ Thị; Tân, Nguyễn Minh; Bảy, Đào Văn; Tuyền, Nguyễn Quang; Huyền Hải, Dương Thị; Huyền Trang, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
This paper presents the synthesis route, the properties of the polynaphthylamine (PNA)/Fe3O4 nanocomposites and their adsorption studies of arsenic (III) removal from water. Microstructure and morphology of the nanocomposites with the polymer contents of 0 %, 5 % and 10 % and 15 % have been investigated by measurements: X-ray diffraction analysis (XRD), SEM, TEM, Raman scattering spectrum. The studied results showed that the size of nanocomposite particles was about 20 nm. The saturation magnetization of the samples had values ​​of about 45-65 emu/g as measured by vibrating sample magnetometer (VSM). The investigations of isothermal adsorption process and influences of pH to arsenic adsorption capacity showed that the nanocomposite materials with appropriate polymer components have good arsenic adsorption ability in water. Keywords: Fe3O4, nanocomposite, magnetization, arsenic treatment